Oral, Vaginal, and Stool Microbial Signatures in Patients With Endometriosis as Potential Diagnostic Non‐Invasive Biomarkers: A Prospective Cohort Study - Hicks, Chloe; Leonardi, Mathew; Chua, Xin‐Yi; Mari‐Breedt, Lisa; Espada, Mercedes; El‐Omar, Emad M.; Condous, George; El‐Assaad, Fatima (BJOG : an international journal of obstetrics and gynaecology, 2025)
ABSTRACT Objective To identify a microbial signature for endometriosis for use as a diagnostic non‐invasive biomarker. Design Prospective cohort pilot study. Setting Nepean Hospital and UNSW Microbiome Research Centre, Australia. Population Sixty‐four age‐ and sex‐matched subjects (n = 19 healthy control (HC); n = 24 non‐endometriosis (N‐ENDO) and n = 21 confirmed endometriosis (ENDO)). All study participants, besides healthy controls, underwent laparoscopic surgical assessment for endometriosis, and histology was performed on excised lesions. Methods Oral, stool and, vaginal samples were self‐collected at a single time point for healthy controls, and preoperatively for patients undergoing laparoscopy. Samples underwent 16S rRNA amplicon sequencing, followed by bioinformatics analysis. Main Outcome Measures Compositional differences between cohorts as identified by diversity analyses, and differentially abundant microbial taxa, as identified by LEfSE analysis. Results The composition of the oral (adjusted p = 0.003), and stool (adjusted p = 0.042) microbiota is different between the three cohorts. Differentially abundant taxa are present within each cohort as identified by LEfSE analysis. Particularly, Fusobacterium was enriched in the oral samples of patients with moderate/severe endometriosis. Conclusions Taxonomic and compositional differences were found between the microbiota in the mouth, gut and, vagina of patients with and without endometriosis and healthy controls. Fusobacterium was enriched in patients with moderate/severe endometriosis. Fusobacterium is noted as a key pathogen in periodontal disease, a common comorbidity in endometriosis. These findings suggest a role for the oral, stool and, vaginal microbiome in endometriosis, and present potential for microbial‐based treatments and the design of a diagnostic swab.